An Ethnographic-Discursive Approach to Parental Self-Help Groups: The Case of ADHD. (June 2016) - Frigerio, Alessandra; Montali, Lorenzo
Mutual aid groups have become a common form of help in the mental health field. Although self-help groups are associated with a range of health and social benefits, they remain poorly understood in terms of the dynamics of their interactions. Adopting an ethnographic-discursive approach, we conducted a 6-month observation of the meetings of a self-help group of parents with children diagnosed with attention deficit/hyperactivity disorder (ADHD) to analyze the discursive dynamics of the interactions that characterized the group. Using a set of discursive strategies and practices, the parents promoted a homogeneity of viewpoints and experiences within the group and constructed a shared and consensual narrative to endorse a specific understanding of ADHD. The production of both homogeneity within the group and a shared narrative served to absolve parents of guilt, helped parents to signify their experience within a blaming social context, and preserved their identities as "good parents."